A cascade synergetic strategy induced by photothermal effect based on platelet exosome nanoparticles for tumor therapy. (March 2022) - Ma, Yuying; Zhang, Yanqin; Han, Ran; Li, Ying; Zhai, Yuewen; Qian, Zhiyu; Gu, Yueqing; Li, Siwen
Abstract: Biomimetic drug delivery systems offer new opportunities to mimic biological components for enhancing tumor targeting efficiency and promoting therapeutic efficacy. Therefore, in this study, the platelet exosomes and photothermal sensitive liposomes were coalesced and incorporated glucose oxidase (GOx, G) and ferric ammonium (FAC, F) to constitute a laser controlled nanosystem (FG@PEL). Results confirmed that FG@PEL possessed two cascade therapeutic strategies. As the first cascade therapeutic strategy, FG@PEL had achieved cascade targeting effect due to the inheritance of biological property of platelet exosomes to adhere cancer cells and respond on the vascular damage triggered by photothermal effect. Subsequently, GOx was used to oxidize glucose to produce hydrogen peroxide which could be catalyzed by FAC to realize cascade reaction for enhancing chemodynamic therapy (CDT). Meanwhile, photothermal effect could accelerate the reaction rate to further improve the therapeutic effect by producing more hydroxyl radicals. So significant therapeutic effect could be acquired through the synergistic modality of FG@PEL, and the mechanism of mutual promotion among different treatment was also clarified. Hence, this research may provide a promising strategy for curative tumor therapy.